On-demand location-aided QoS routing in ad hoc networks - Huang, C.; Dai, F.; Wu, J. (International Conference on Parallel Processing, 2004. ICPP 2004, 2004)
With the development and application of position devices, location-based routing has received growing attention. However, little study has been done on QoS routing with the aid of location information. The existing location-based routing approaches, such as flooding-based routing schemes and localized routing schemes, have their limitations. Motivated by ticket-based routing, we propose an on-demand location-aided, ticket-based QoS routing protocol (LTBR). Two special cases of LTBR, LTBR-1 and LTBR-2, are discussed in detail. LTBR-1 uses a single ticket to find a route satisfying a given QoS constraint. LTBR-2 uses multiple tickets to search valid routes in a limited area. All tickets are guided via both location and QoS information. LTBR has lower overhead compared with the original ticket-based routing, because it does not rely on an underlying routing table. On the other hand, LTBR can find routes with better QoS qualities than traditional location-based protocols. Our simulation results show that LTBR-1 can find high quality routes in relatively dense networks with high probability and very low overhead. In sparse networks, LTBR-2 can be used to enhance the probability of finding high quality routes with acceptable overhead.